Parry– Romberg Syndrome: A Case Report (Nepalese Journal of Radiology, 2014)
The purpose of this report is to present radiological features of a rare entity called Parry-Romberg syndrome (also known as Progressive hemifacial atrophy). The authors report one rare case of a 18 year old female patient with Parry-Romberg syndrome, accompanied by a brief review of literature and various radiological features of this entity. Final diagnosis of a Parry-Romberg syndrome was made on clinical and radiological grounds. Radiologists should be familiar with various radiographic, CT and MRI findings observed in this disorder. DOI: http://dx.doi.org/10.3126/njr.v4i1.11571 Nepalese Journal of Radiology, Vol.4(1) 2014: 67-70